1992
DOI: 10.1016/0006-8993(92)91536-n
|View full text |Cite
|
Sign up to set email alerts
|

Androgen and estrogen concentrating neurons in chemosensory pathways of the male Syrian hamster brain

Abstract: The medial preoptic area (MPOA), bed nucleus of the stria terminalis (BNST), and medial amygdaloid nucleus (Me) are essential for male sexual behavior in the Syrian hamster. These nuclei received chemosensory stimuli and gonadal steroid signals, both of which are required for mating behavior. The objective of this study was to compare the distribution of androgen- and estrogen-concentrating neurons in MPOA, BNST, and Me in the adult male hamster using steroid autoradiography for estradiol (E2), testosterone (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
48
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(54 citation statements)
references
References 36 publications
6
48
0
Order By: Relevance
“…Studies of AR, ER· and ERß in other avian species besides quail have found similar patterns of high expression for the mRNA and/or protein of these important components of steroid hormone action in Tn [Arnold et al, 1976;Balthazart et al, 1992;Gahr et al, 1993;Ball et al, 1999;Bernard et al, 1999]. The medial amygdala in rats exhibits a similar pattern of expression for both of these three types of sex steroid receptors [Wood et al, 1992;Wood and Newman, 1995a;Kuiper et al, 1998]. However, a critical examination of the connectivity of this nucleus does not necessarily support the proposition that Tn is homologous to the mammalian Me.…”
Section: Discussionmentioning
confidence: 92%
“…Studies of AR, ER· and ERß in other avian species besides quail have found similar patterns of high expression for the mRNA and/or protein of these important components of steroid hormone action in Tn [Arnold et al, 1976;Balthazart et al, 1992;Gahr et al, 1993;Ball et al, 1999;Bernard et al, 1999]. The medial amygdala in rats exhibits a similar pattern of expression for both of these three types of sex steroid receptors [Wood et al, 1992;Wood and Newman, 1995a;Kuiper et al, 1998]. However, a critical examination of the connectivity of this nucleus does not necessarily support the proposition that Tn is homologous to the mammalian Me.…”
Section: Discussionmentioning
confidence: 92%
“…In mammals, gonadal steroids have been shown to control the behavioral responses to pheromones by actions on the central nervous system (22). Several studies have localized receptors for gonadal steroids within neurons (23). It is suggested that steroids could influence the behavior by regulating the synaptic transmission between peripheral neurons and more central areas.…”
Section: Discussionmentioning
confidence: 99%
“…To determine when androgen receptors first appear in hamster FMNs, an AR immunocytochemistry time-course study using PG-21, an anti-AR antibody that has been well documented in the hamster (Wood et al, 1992;Wood and Newman, 1993Romeo et al, 2000), was performed on brainstem tissue sections from males and females ranging in age from P0 to P10. The AR is a steroid receptor that resides in the cytoplasm in an unliganded state and, after ligand binding, translocates to the nucleus (Kumar and Thompson, 1999;Aranda and Pascual, 2001).…”
Section: Ars First Appear In Developing Hamster Fmns By P2 In Males Amentioning
confidence: 99%